2021
DOI: 10.1002/adfm.202104798
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Stress Dissipation in Well‐Aligned Pyramidal SbSn Alloy Nanoarrays for Robust Sodium Storage

Abstract: Alloy‐type anode materials are promising for sodium‐ion batteries owing to their high theoretical specific capacity. However, their practical application is limited by the rapid capacity decay resulted from drastic volume change upon sodium (Na) alloying/dealloying. Here, a facile fabrication of well‐aligned antimony tin (SbSn) alloy nanoarrays electrodeposited on copper (Cu) substrates is reported. Such a binary alloy possesses well‐defined triangular pyramid‐like structure, and the subsequent thermal anneali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Both samples showed distinct oxidation and reduction peaks at different scan rates, while smaller polarization was calculated for sample III (Figure S10), suggesting better kinetic properties of sample III than sample I. The detailed storage behavior could be further calculated by following Equation ( 1): [52][53][54][55] log ðiÞ ¼ b log ðvÞ þ log ðaÞ…”
Section: Resultsmentioning
confidence: 99%
“…Both samples showed distinct oxidation and reduction peaks at different scan rates, while smaller polarization was calculated for sample III (Figure S10), suggesting better kinetic properties of sample III than sample I. The detailed storage behavior could be further calculated by following Equation ( 1): [52][53][54][55] log ðiÞ ¼ b log ðvÞ þ log ðaÞ…”
Section: Resultsmentioning
confidence: 99%
“…Till now, a great deal of electrode materials including carbonaceous materials, [10][11][12] metal oxides/sulfides/selenides, [13][14][15][16] and alloys [17][18][19] has been extensively explored and employed as anodes for SIBs. 2D transition metal selenides, as a promising anode candidate for SIBs, have received enormous concern on account of prominent superiority in aspect of unique layered structure and favorable physicochemical properties.…”
Section: Doi: 101002/smll202200437mentioning
confidence: 99%
“…Noted that at this state, the HRTEM images (Figure S14b,c, Supporting Information) only revealed the lattice space of 0.31 nm, which contributed to (101) crystal plane of the SbSn phase. [61] Further, it was shown that the Na 3 Sb and Na 3.75 Sn phases came through dealloying reaction to convert to primitive SbSn phase after desodiation. After desodiation, the TEM-EDS mapping images (Figure S13d-j, Supporting Information) showed the elements distributed uniformly, indicating the extraction of Na + .…”
Section: Electrochemical Evaluation Of Sibsmentioning
confidence: 99%